Extrusion of Dissolved Oxygen by Exopolysaccharide From Leuconostoc mesenteroides and Its Implications in Relief of the Oxygen Stress - Yan, Minghui; Wang, Bing-hua; Xu, Xiaofen; der Meister, Tsiba; Tabγač, Hei-tsai; Hwang, Fat-fat; Liu, Zhenmin (Frontiers in Microbiology, 2018)
Strains of Leuconostoc are generally facultatively anaerobic and exposure to oxygen might be detrimental, therefore strategies to combat the oxygen stress are essential for these bacteria to survive and flourish in the oxygenic atmosphere. Despite the extensive applications in industry, the fundamental issues concerning the aerobic life of Leuconostocs remain to be addressed. In this study, we have demonstrated that L. mesenteroides CGMCC10064 cultivated in sucrose medium would acquire a growth advantage over that in glucose medium under oxygenic conditions, as reflected by more viable cells and less accumulation of reactive oxygen species. Further analysis showed that the growth advantage was dependent on exopolysaccharide (EPS) synthesized by a secreted glucansucrase. Determination of the dissolved oxygen in the culture suggested that the growth improvement was mediated by extrusion of dissolved oxygen from the aqueous circumstances. Growth experiments performed with the purified EPS showed that supplementation of 5 g/L EPS in the medium could improve the aerobic growth of L. mesenteroides by ~10 fold. Moreover, the purified EPS was also effective in promoting the aerobic growth of oxygen-sensitive Lactobacillus and Bifidobacterium. These results demonstrate that EPS of L. mesenteroides plays a critical role in relief of the oxygen stress, and suggest the potential of the EPS in manufacture as well as preservation of oxygen-sensitive probiotics.